Drink monitoring for self and others: precollege drinkers and the Bad-Habit-Formation Hypothesis. (4th May 2019) - Jensen, Jakob D.; John, Kevin K.; Freeman, Jason; Carcioppolo, Nick; Pokharel, Manusheela
Abstract: Background: Past research has demonstrated that precollege alcohol consumption is related to college alcohol consumption. But whether precollege drinking is also related to drinking-related behaviors, such as drink monitoring, is unknown. Some have argued that precollege drinking, as a form of experience, should be related to the performance of positive drinking-related behaviors ( learning-from-experience hypothesis ) whereas others have argued that, given the environment of precollege drinkers, it should be related to negative drinking-related behaviors ( bad-habit-formation hypothesis ). Methods: A cross-sectional survey of college students ( n  = 284) at a large Midwestern university in the U.S. Participants completed measures of precollege drinking, college drinking, fraternity membership, and responsible drinking behaviors. Results: Precollege drinkers were more likely to engage in college drinking; the former explained 12% of the variance in the College Drinking Scale, above and beyond other predictors. Precollege drinkers were less likely to monitor their own alcohol consumption or the consumption of their friends. Conclusions: Precollege drinkers were less likely to monitor their own drinking and the drinking of friends, consistent with the bad-habit-formation hypothesis ; that is, the notion that early drinking experiences cultivate the formation of irresponsible drinking behaviors.